Bovine herpes virus-1 (BoHV-1) detection in dairy cattle with reproductive problems in Sudan (Journal of Advanced Veterinary and Animal Research, 2015)
The present work aimed to observe the infection pattern of Bovine herpes virus-1 (BoHV-1) in dairy cattle with reproductive problems in Sudan. A total of 140 samples comprising of vaginal swab (n=97), placenta (n=15), whole blood (n=19), uterine fluid (n=1), and serum (n=8) were collected from 16 dairy herds showing particularly high rate of abortion and infertility in Khartoum State. The samples were used for virus isolation, and were tested by Enzyme-Linked Immunosorbent Assay (ELISA) and polymerase chain reaction (PCR). No virus could be isolated from the samples inoculated for isolation in cell culture. Out of 80 specimens tested by ELISA, 7 (8.75%) were found to be positive, and one sample was doubtful. Using PCR, 11 (10.7%) out of 103 samples were found to be positive. When comparing between two methods for DNA extraction, the DNA extracted by commercial kit was found to be better in quality as compared to the DNA extracted using phenol/chloroform/isoamyl-alcohol method. The study confirmed the presence of BoHV-1 in cattle farms with reproductive problems in Sudan. http://dx.doi.org/10.5455/javar.2015.b81